2020
DOI: 10.3390/en13112994
|View full text |Cite
|
Sign up to set email alerts
|

Universal Kinetic Model to Simulate Two-Step Biodiesel Production from Vegetable Oil

Abstract: To date, to simulate biodiesel production, kinetic models from different authors have been provided, each one usually applied to the use of a specific vegetable oil and experimental conditions. Models, which may include esterification, besides transesterification simulation, were validated with their own experimental conditions and raw material. Moreover, information about the intermediate reaction steps, besides catalyst concentration variation, is either rare or nonexistent. Here, in this work, a universal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…A variety of kinetic studies can be found in the literature in which important simplifications were adopted, such as considering the reactions irreversible [8][9][10] or neglecting the presence of partially converted intermediates (i.e., diglycerides and monoglycerides) [11]. In addition, many kinetic models reported in the literature do not take into consideration explicitly a very important variable such as the catalyst concentration, though some relevant studies do include it in the reaction rate equations [12,13]. Saponification reactions of glycerides and methyl esters have been also included in other models [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of kinetic studies can be found in the literature in which important simplifications were adopted, such as considering the reactions irreversible [8][9][10] or neglecting the presence of partially converted intermediates (i.e., diglycerides and monoglycerides) [11]. In addition, many kinetic models reported in the literature do not take into consideration explicitly a very important variable such as the catalyst concentration, though some relevant studies do include it in the reaction rate equations [12,13]. Saponification reactions of glycerides and methyl esters have been also included in other models [14][15][16].…”
Section: Introductionmentioning
confidence: 99%